Creating Our Own Spaces: Disruptive Approaches to Educational Leadership Research. Issue 2 (March 2023) - Duarte, Bryan J.; Cordova, Amanda J.
Our work seeks to reflexively make visible the blurring of binary markers at the intersection of our research, sexuality, gender, and professional socialization as a necessary disruption to liberate our intersectional possibilities in the making. We argue the queering of educational leadership is met by the intimate and layered experiences of identity dismemberment operating to tarnish, devalue, and displace the wealth of intersectional knowledge. The ultimate goal is to subjugate the researcher; to trace a stencil of a binary identity whereby the image of the non-binary cannot be conjured as contributors to epistemology, theory, methodology, pedagogy, leadership, or practice. We utilize testimonios to interrogate how these lines were drawn from the everyday of academic life to blur the binary; to conjure the queer in every nook and cranny of experiences until the reification of whiteness, patriarchy, and sexuality is made a mess from which prescribed lines can no longer be drawn. We assert the toll of securing this "way" positioned us in a binary, more often than not, to research about queerness without any overlap in the praxis of queerness in the relationships, institutions, and teaching that guard the landscape of "being" in Educational Leadership. In doing so, we position the (re)membering of our identities at the intersection of Queer and Chicana Feminist theoretical perspectives to theorize a third space to heal and build a leadership practice in our image.